A new parallel greedy bit-loading algorithm with fairness for multiple users in a DMT system - Akujuobi, C.M.; Jie Shen; Sadiku, M.N.O. (IEEE transactions on communications, 2006)
This letter first reviews the multiuser bit-loading algorithms for discrete multitone systems. Then an improved algorithm is proposed, which allows several users to get additional bits in parallel. It reduces the number of iterations dramatically. A new fairness coefficient is also introduced to reduce the variance of the data rate among users